Optimization of a Niosomal Transdermal Delivery System Containing Kojic Acid and Alpha Arbutin - Nurfitrah Daud; Mahdalena Sy Pakaya; Faradila Ratu Cindana Mo’o; Faramita Hiola; La Ode Aman (Jurnal Farmasi Teknologi Sediaan dan Kosmetika, 2026)
Hyperpigmentation is a skin disorder characterized by excessive melanin production. Kojic acid and alpha-arbutin are skin-lightening agents that inhibit tyrosinase activity; however, their effectiveness is limited by poor skin penetration. This study aimed to formulate and characterize a niosomal transdermal delivery system containing a combination of kojic acid and alpha-arbutin at different Span 80 concentrations. Niosomes were prepared using the ethanol injection method in three formulations: F1 (0.37% Span 80), F2 (0.40% Span 80), and F3 (0.42% Span 80). The formulations were evaluated for organoleptic properties, viscosity, pH, stability, irritation potential, particle size, polydispersity index (PDI), and zeta potential. All formulations exhibited acceptable physical characteristics, remained stable, and caused no irritation. The particle sizes of F1, F2, and F3 were 185.1 nm, 372.9 nm, and 322.6 nm, respectively, with corresponding PDI values of 0.273, 0.295, and 0.118. The zeta potential values were -18.5 mV, -23.0 mV, and -18.4 mV for F1, F2, and F3, respectively. Statistical analysis showed that variation in Span 80 concentration had no significant effect on viscosity or pH (p > 0.05). The combination of kojic acid and alpha-arbutin was successfully incorporated into a niosomal system with favorable physicochemical characteristics, and Formula III was identified as the optimal formulation.